1999
DOI: 10.1677/jme.0.0220037
|View full text |Cite
|
Sign up to set email alerts
|

Differential immunolocalization of estrogen receptor alpha and beta in rat ovary and uterus

Abstract: In order to investigate the localization of estrogen receptor (ER) and ER in the reproductive organs in the rat, polyclonal antibodies were raised to each specific amino acid sequence. The Western blot with anti-ER antibody showed a 66 kDa band in rat ovary and uterus, while that with anti-ER antibody detected a 55 kDa band in rat ovary, uterus and prostate. The ligand-independent nuclear localization of the two receptors was verified by immunocytochemistry. By immunohistochemistry, the nuclei of glandular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 44 publications
11
91
2
1
Order By: Relevance
“…For example, bone predominantly expresses ERα, except in the marrow which is primarily ERβ [63]. Similarly, in the uterus, ERα is greater but ERβ is expressed in the glandular epithelium [57,67]. A point of particular clinical relevance is that ERα is the target of E 2 's trophic effects in mammary and uterine tissue [63].…”
Section: Erβ-mediated Actions In the Hippocampus For E 2 'S Functionamentioning
confidence: 99%
“…For example, bone predominantly expresses ERα, except in the marrow which is primarily ERβ [63]. Similarly, in the uterus, ERα is greater but ERβ is expressed in the glandular epithelium [57,67]. A point of particular clinical relevance is that ERα is the target of E 2 's trophic effects in mammary and uterine tissue [63].…”
Section: Erβ-mediated Actions In the Hippocampus For E 2 'S Functionamentioning
confidence: 99%
“…These findings are very similar to previous findings (Fitzpatrick et al 1999, Sar & Welsch 1999 indicating that, by immunocytochemistry, ER but not ER could be detected in the oviduct and uterus. Hiroi et al (1999) have reported that, in the rat uterus, the nuclei of glandular and luminal epithelial cells were also immunostained with ER antibodies and that only the nuclei of glandular epithelium cells were stained with anti-ER . Since RT-PCR analysis has shown low expression of ER mRNA in the rat uterus , it is possible that the approaches used in the present study were not sensitive enough to detect low amounts of ER at the cellular level.…”
Section: Female Reproductive Organsmentioning
confidence: 99%
“…Both receptors are expressed in adult and immature ovary, the ER␣ protein being detected in interstitial and theca cells and the ER␤ protein in granulosa cells (Fitzpatrick et al, 1999;Hiroi et al, 1999;O'Brien et al, 1999;Sar and Welsch, 1999). Analysis of single and compound mutant mice for ER␣ and ER␤ has provided evidence that each receptor is required for specific ovarian functions, namely follicular development (ER␤) and ovulation (ER␣) (Dupont et al, 2000).…”
Section: Introductionmentioning
confidence: 99%